Biodegradation of ibuprofen and metformin by bacteria isolated from Chihuahua, Mexico - Soto, Marisela (2024)
Metformin is one of the medications used to treat non-insulin-dependent diabetes mellitus, and ibuprofen is one of the most used non-steroidal anti-inflammatory drugs worldwide. The use of these pharmaceuticals has currently generated contamination of rivers and soil since they are highly stable compounds. Therefore, the objective of this work was to evaluate the biodegradation of ibuprofen and metformin by bacteria of the genus Bacillus, Paenibacillus, and Pseudomonas isolated from sediments of bodies of water in the state of Chihuahua. Regarding the removal of ibuprofen, the Bacillus strain showed the highest removal values of 52.53% at 480 h, while Pseudomonas and Paenibacillus reached 42.93% and 44.8%, respectively. On the other hand, 99.99% of the removal of metformin was observed by the Pseudomonas strain at 480 h; Bacillus and Paenibacillus strains showed a removal of 97.79% and 92.36%, respectively. Thus, it is concluded that the use of the bacterial strains isolated in this study is a promising alternative for the treatment of pharmaceutical products that currently have environmental risks.